Moderating Role of MSME Collaboration on Digital Innovation Toward Adaptive Capability and MSME Performance in Indonesia - Antonius Ary Setyawan; Endang Setyawati; Jaluanto Sunu Punjul Tyoso (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study investigates the effect of digital innovation on MSME performance in Indonesia, focusing on the mediating role of digital adaptive capability and the moderating effect of MSME collaboration. Drawing on the Dynamic Capabilities Theory, a structural equation model was developed and tested using data from 100 MSMEs across various sectors. The results indicate that digital innovation has a significant direct effect on performance and also enhances adaptive capability. However, adaptive capability itself does not significantly influence performance, suggesting it may require complementary factors to be effective. Contrary to expectations, MSME collaboration did not moderate the effects of innovation or adaptive capability on performance, implying that collaboration must be strategically aligned to be beneficial. The findings highlight the need for MSMEs to focus on internal digital readiness while being cautious about over-relying on external partnerships. The study contributes to the digital transformation literature in emerging economies and provides practical guidance for MSME policy and strategy. Future research is recommended to use longitudinal data and explore additional moderators or mediators in the innovation–performance relationship.